Vulnerabilidade à seca e (i)mobilidade no Nordeste brasileiro: partir ou resistir? - Correia, Isac Alves; Barbieri, Alisson Flávio (Sustainability in Debate, 2019)
Based on a survey with 1,064 households in the Seridó Potiguar, in the Brazilian northeastern Semiarid region, this paper discusses how individuals adjust mobility responses when they perceive the impacts of droughts on their livelihoods. Our results show that short-term responses are more common with daily or seasonal mobility in relation to permanent residence change. We also observe a greater female participation in these types of mobility, probably due to its shorter distance. Cash transfer programs show great relevance in this process, supporting families without emigrants or subsidizing the emigration of at least one resident. Finally, we conclude that migration and/or labor supply in urban areas have been important strategies for families to deal with the risk, which requires strong institutions to manage the potential negative impacts on the destination regions of these individuals.